2018
DOI: 10.1016/j.antiviral.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

IRF-1, RIG-I and MDA5 display potent antiviral activities against norovirus coordinately induced by different types of interferons

Abstract: Norovirus represents the main cause of acute nonbacterial gastroenteritis worldwide. In immunocompromised patients, it bears high risk of causing chronic infection with significant morbidity and mortality. The lack of specific treatment prompts the development of anti-norovirus agents. In this study, we have investigated the role of interferon (IFN) response and evaluated antiviral activities of different IFNs against human norovirus (HuNoV) replication using a HuNoV replicon model. We found that HuNoV RNA rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 39 publications
1
33
1
Order By: Relevance
“…Similarly, down-regulation of ISRE-dependent genes in HGT-NV when compared to HGT-Cured cells, which have silenced the IFNLR1 gene to the same extent, put forward the idea that HuNoV replication induces IFN-dependent responses. In line with this, a recent study using the same replicon identified RIG-I and MDA5 proteins as potent negative regulator of HuNoV replication suggesting that viral RNA secondary structures can readily be detected during replication (Dang et al, 2018). These observations are however in striking contrast to the study of Qu and colleagues in which transfection of stool-derived HuNoV RNA readily replicated in 293T cells but failed to induce detectable interferon responses (Qu et al ., 2016).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Similarly, down-regulation of ISRE-dependent genes in HGT-NV when compared to HGT-Cured cells, which have silenced the IFNLR1 gene to the same extent, put forward the idea that HuNoV replication induces IFN-dependent responses. In line with this, a recent study using the same replicon identified RIG-I and MDA5 proteins as potent negative regulator of HuNoV replication suggesting that viral RNA secondary structures can readily be detected during replication (Dang et al, 2018). These observations are however in striking contrast to the study of Qu and colleagues in which transfection of stool-derived HuNoV RNA readily replicated in 293T cells but failed to induce detectable interferon responses (Qu et al ., 2016).…”
Section: Discussionmentioning
confidence: 59%
“…Influence of lambda interferons on murine noroviruses has been highlighted in previous studies using different experimental setups (Baldridge et al ., 2015; Baldridge et al ., 2017; Rocha-Pereira et al ., 2018b). In the case of the human norovirus, recent work using the same replicon in Huh-7 human hepatoma cell line showed that all three types of IFN, when exogenously added, were able to inhibit HuNoV replication leading to virus clearance during long-term treatment (Dang et al ., 2018). However, it is not known whether physiological activation of the interferon pathways, particularly, the lambda IFN signalling pathway exerts an antiviral effect against human noroviruses.…”
Section: Discussionmentioning
confidence: 99%
“…RAD51AP1 facilitates homologous recombination of host DNA [107], while SEC61G functions in membrane protein translocation and incorporation into the endoplasmic reticulum [108]. The interactions between HuNoV and these genes are speculative; however IRF3 [109,110], IRF7 [110,111], MDA5 [112][113][114][115], RIG-I [35,111,113,114], TLR3 [112], and TLR7 [114,116,117] have been previously implicated in NoV responses. Of note, TLR2 enhances cytokine production upon the detection of rotavirus [118].…”
Section: Discussionmentioning
confidence: 99%
“…A molecular hallmark of lupus erythematosus lesions is the high expression of interferon (IFN)-stimulated genes (ISGs) 9 15 16. These include myxovirus protein A ( MxA ),17 IFN inducible protein 6 ( IFI6 ), CXCL9 , CXCL10 , 2,5-oligoadenylate synthase ( OAS ) including OAS2 and OASL , IFN-induced helicase C domain-containing protein 1 ( IFIH1/MDA5 ), bone marrow stromal antigen 2 ( BST2 ) and guanylate-binding protein 1 ( GBP1 ) in CLE lesions 8 18–21. It is well known that IFNs induce expression of major histocompatibility complex (MHC) class I and MHC class I-pathway related molecules (β2 microglobulin, β2M) and this has also been reported for organ-cultured human scalp skin 22–24.…”
Section: Introductionmentioning
confidence: 99%